16‐Year follow‐up of an avulsed maxillary central incisor after replantation following 10‐h storage: An unusual case. (19th June 2017) - Kırzıoğlu, Zuhal; Erken Güngör, Özge; Erdoğan, Yıldırım
ABSTRACT: Tooth avulsion is a type of dental injury defined as the complete displacement of a tooth out of the alveolar socket, and the lack of prompt treatment measures can result in the loss of function, poor quality of life, and psychological and social problems. However, several factors may not permit the immediate replantation of an avulsed tooth; therefore, delayed replantation has emerged as an alternative to meet the esthetic, functional, and psychological demands of patients. Here it was described that the successful replantation of an avulsed maxillary central incisor in a 9‐year‐old boy who presented at the clinic with the tooth stored in unfavorable conditions as dry and then in olive oil‐milk mixture almost 10 h after the event. The tooth has remained in its socket healthy for 16 years after treatment. The patient was satisfied with both esthetics and function.